Turkish family with Dysequilibrium syndrome with a novel mutation in the VLDLR gene. - Muhsin Elmas; Basak Gogus; Ayse Tolunay Oflu; Aysegul Bukulmez; Ebru Elmas; Mustafa Solak (Journal of Biochemical and Clinical Genetics, 2019)
Background: A very few diseases are reported caused due to cerebellar hypoplasia and neuronal migration defects like pachygyria. Cerebellar Ataxia, mental retardation, and Dysequilibrium Syndrome 1 (DES) (OMIM # 224050) are one among such group of diseases. DES is caused due to a homozygous mutation in the VLDLR gene involved majorly in neuronal migration. Case Presentation: Two members (siblings) from a Turkish family presented with neuromotor developmental delay, moderate learning disability, delayed psychosocial development and strabismus complaints. Whole exome sequencing (WES) was performed as consanguinity existed between the parents and specific pre-diagnosis could not provide a satisfactory conclusion for the patients. WES revealed a homozygote novel mutation in the VLDLR gene. Conclusion: Evaluation of WES data resembled a process of finding a needle in a haystack; therefore, the present study recommended clinical information and anamnesis to be very important in understanding and interpreting the WES result. [JBCGenetics 2019; 2(1.000): 77-80]